The Reuse of Ceramic Materials in Architectural Design – Case Studies - MAGOSZ Agata (Architecture, Civil Engineering, Environment)
The global construction industry, notorious for resource consumption and waste production, has found an interest in the circular economy and sustainable development practices. This paper examines the reusability of ceramic building materials within architectural designs, emphasizing the principles of the circular economy and the 3R concept with a special focus on reuse. By performing a comparative analysis of 26 buildings the research explores the strategies for reusing ceramic materials. It categorizes reuse into two approaches: re-creation and transformation, while also considering the prevention of materials from becoming waste. The analysis scrutinizes the origin and function of materials, their placement in new designs, and the reasons behind their reuse. The study delineates recurring design patterns of using reclaimed building materials. It also categorizes three main approaches to incorporating reused elements into new structures.